Gender Fair Participation for Girls in Co-Curricular Activities (CCA): Barriers and Enablers in Pakistan’s Education - Uzair-ul-Hassan, Muhammad; Parveen, Iram; Mishal; De Souza, Joiciane (Pakistan Journal of Humanities and Social Sciences, 2023)
Co-Curricular Activities (CCA) are the part of the students’ life and a way of developing a student holistically. There are different studies which showed that the participation of girls in sports is lower than the boys. Low participation indicates that there are some reasons behind this. As females are an equal and important component of society, therefore, it is essential to enhance the participation of girls in sports for their health and brighter future. The main purpose of the study was to explore the restraining factors in equal gender participation in co-curricular activities in higher education institutions in Sargodha-Pakistan. The current study was mixed method in nature. The population was consisted of all girls who were studying in general public universities of Punjab province. A total of three hundred girls were selected as sample for collecting quantitative data while eight girls were selected for collecting qualitative data. Respondents were selected by multi-stage sampling technique. Data were collected through self-generated questionnaire having forty seven statements and through interview protocol having seven questions. Quantitative data were analysed through SPSS while interviews were analysed through thematic analysis. Percentage, independent sample t-test and one way ANOVA were used for quantitative data analysis. Both the results and discussion visibly showed that there exists familial, institutional and societal barriers involved in equal and fair gender participation of girls in co-curricular. It is recommended that higher education institutions should play their role in making strategic reforms to overcome such barriers which are restraining factors for all girls that make them hesitant to participate in co-curricular activities in universities in Pakistan.